Quinoxaline derivatives as attractive electron-transporting materials - Abid, Zeeshan; Ali, Liaqat; Gulzar, Sughra; Wahad, Faiza; Ashraf, Raja Shahid; Nielsen, Christian B. (Beilstein Journal of Organic Chemistry, 2023)
This review article provides a comprehensive overview of recent advancements in electron transport materials derived from quinoxaline, along with their applications in various electronic devices. We focus on their utilization in organic solar cells (OSCs), dye-sensitized solar cells (DSSCs), organic field-effect transistors (OFETs), organic-light emitting diodes (OLEDs) and other organic electronic technologies. Notably, the potential of quinoxaline derivatives as non-fullerene acceptors in OSCs, auxiliary acceptors and bridging materials in DSSCs, and n-type semiconductors in transistor devices is discussed in detail. Additionally, their significance as thermally activated delayed fluorescence emitters and chromophores for OLEDs, sensors and electrochromic devices is explored. The review emphasizes the remarkable characteristics and versatility of quinoxaline derivatives in electron transport applications. Furthermore, ongoing research efforts aimed at enhancing their performance and addressing key challenges in various applications are presented.
Keywords: electron transport materials; non-fullerene acceptors; n-type semiconductors; organic electronics; quinoxalines